2014
DOI: 10.1176/appi.ps.201300213
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Behavioral Therapy for Medication-Resistant Psychosis: A Meta-Analytic Review

Abstract: Patients with schizophrenia often continue to experience disabling positive symptoms, despite adequate trials of medication. In these situations, patients may be prescribed an adjunctive medication, but a more effective choice may be cognitive-behavioral therapy (CBT). This review of 16 published articles from 12 randomized controlled trials found that CBT was associated with robust improvements in the positive symptoms of psychotic disorders. In addition, the improvements were sustained at follow-up, the auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(113 citation statements)
references
References 58 publications
3
109
0
Order By: Relevance
“…These changes correspond to the treatment focus on persisting positive symptoms, and the effect sizes appear comparable with the small-to-medium effects observed in similar trials of CBTp. 33,34 However, caution is warranted because no significant group differences in favour of ACT were observed for the other outcome measures, and the befriending group unexpectedly showed significantly greater improvement in reported delusional distress, with a medium effect at follow-up. Additionally, no group differences were evident for any of the process measures.…”
Section: Discussionmentioning
confidence: 97%
“…These changes correspond to the treatment focus on persisting positive symptoms, and the effect sizes appear comparable with the small-to-medium effects observed in similar trials of CBTp. 33,34 However, caution is warranted because no significant group differences in favour of ACT were observed for the other outcome measures, and the befriending group unexpectedly showed significantly greater improvement in reported delusional distress, with a medium effect at follow-up. Additionally, no group differences were evident for any of the process measures.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, at least seventeen meta-analyses conducted in the last decade, and half of them revealed inconsistent findings regarding the efficacy of CBTp. Meta-analyses indicated small to large effect sizes ranging from 0.21 to 1.31 for positive symptoms (53-61), 0.21 to 1.08 for negative symptoms (56,57,59,61), and from 0.21 (in favor of CBTp) to 0.65 for general psychopathology (53,57,61,62). However, several recent meta-analyses have suggested that CBTp has no significant effect on positive or negative symptoms, or overall psychopathology (g<0.2) (63)(64)(65).…”
Section: Cognitive Behavior Therapy For Psychosismentioning
confidence: 99%
“…DLPFC: dorsolateral prefrontal cortex shown that persistent symptoms, particularly delusions and depression, can be reduced by cognitive behaviour therapy for psychosis (CBTp) in such patients with medication-refractory symptoms [6][7][8]. More recent studies also indicate a role for CBTp in the prevention of psychosis [9,10].…”
Section: Neuroimaging Predictors Of Long Term Outcome Following Cbtpmentioning
confidence: 99%
“…However, not all patients respond equally well to it. Symptom reduction with CBTp is seen with modest effect sizes and found to a noticeable degree in only about 50% of patients who undergo this therapy [6][7][8]. Furthermore, according to a recent meta-analysis, the effect size for symptom reduction following CBTp may be even smaller when sources of potential bias, such as masking of outcome assessments, are controlled for [19].…”
Section: Neuroimaging Predictors Of Long Term Outcome Following Cbtpmentioning
confidence: 99%